2009
DOI: 10.1186/1757-7241-17-50
|View full text |Cite
|
Sign up to set email alerts
|

Management of a massive thoracoabdominal impalement: a case report

Abstract: A 26 year old male was impaled through his chest and upper abdomen with an iron angle, one and half meter long and five centimeters thick. The iron angle entered the chest, through the epigastrium and exited posteriorly just inferior to the angle of left scapula. The patient was transported to hospital with the iron angle in situ. Positioning the patient for intubation proved a major challenge. An unconventional position for intubation allowed a successful airway management. Paucity of time prevented us from g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 12 publications
(9 reference statements)
0
33
0
Order By: Relevance
“…Thoracoabdominal impalement is one of the most severe types of penetrating trauma injuries [1]. These injuries usually involve vital organs such as the heart, lung, or the great vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thoracoabdominal impalement is one of the most severe types of penetrating trauma injuries [1]. These injuries usually involve vital organs such as the heart, lung, or the great vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Fatal conditions such as hypoxemia, airway obstruction, hemorrhage, cardiac tamponade, and aspiration can lead to death within 30 minutes to 3 hours. However, it is reported that patients with these conditions who are immediately transferred alive to a hospital have a high probability of survival [1,2]. Therefore, cautious extrication from the scene and rapid transportation to a trauma center are crucial factors for a survival outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these should be avoided or administered in titrated doses in haemodynamically unstable patients or in patients with suspected cardiovascular compromise. Ketamine is considered useful to induce anaesthesia in patients with cardiac tamponade, which produces stimulation of the sympathetic nervous system [7]. Also, use of lidocaine on anaesthetic inductions may be useful once cardiovascular compromise is present.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…The prehospital phase of care is even more crucial. The main goals in thoracic trauma resuscitation include optimizing tissues oxygen delivery, bleeding control and replacement of intravascular volume [7].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
See 1 more Smart Citation